A national survey of aged care facility managers' views of preparedness for natural disasters relevant to residents with dementia. (21st February 2019) - Schnitker, Linda; Fielding, Elaine; MacAndrew, Margaret; Beattie, Elizabeth; Lie, David; FitzGerald, Gerard
Abstract : Objective: The aim was to explore the natural disaster preparedness strategies of Australian residential aged care facilities (RACFs), focussing on aspects relevant to people with dementia. Methods: An online survey was sent to 2617 RACF managers, with 416 responding. Questions included the following: (a) demographics; (b) presence and detail level of disaster/evacuation plans; and (c) references to people with dementia. Results: One in four facilities had experienced a natural disaster in the previous five years. The majority had plans for natural disaster and evacuation. Two‐thirds recognised the unique needs of people with dementia. Managers anticipated that residents with dementia would require more staff time and resources and might become disoriented. Conclusions: Gaps identified in existing RACF evacuation plans highlighted challenges in ensuring the ongoing safety and care of residents, especially those with dementia. Facilities need to have adequate plans and processes that minimise the potential risks of natural disasters.